Haplotypes of the HLA-G 3′ untranslated region respond to endogenous factors of HLA-G+ and HLA-G- cell lines differentially - Poras, Isabelle; Yaghi, Layale; Martelli-Palomino, Gustavo; Mendes, Celso T.; Muniz, Yara Costa Netto; Cagnin, Natalia F.; De Almeida, Bibiana Sgorla; Castelli, Erick C. [UNESP]; Carosella, Edgardo D.; Donadi, Eduardo A.; Moreau, Philippe (Public Library of Science (PLoS), 2017)
The immune checkpoint HLA-G prevents maternal rejection of the fetus and contributes in cancer invasion and acceptance of allografts. The 5′ and 3′ regulatory regions of the HLA-G gene are polymorphic and balancing selection probably maintains this variability. It is proposed that nucleotide variations may affect the level of HLA-G expression. To investigate this issue we aimed to analyze how haplotypes of the 3′ untranslated region (3′UTR) with highest worldwide frequencies, namely UTR-1, UTR-2, UTR-3, UTR-4, UTR-5, UTR-18 and UTR-7, impact the expression of a luciferase reporter gene in vitro. Experiments performed with the HLA-G positive cell lines JEG-3 (choricarcinoma) and FON (melanoma), and with the HLA-G negative cell lines M8 (melanoma) and U251MG (glioblastoma) showed that the HLA-G 3′UTR polymorphism influences the response to endogenous cellular factors and may vary according to the cell type. UTR-5 and UTR-7 impact the activity of luciferase the most whereas UTR-2, UTR-3, UTR-4, and UTR-18 have intermediate impact, and UTR-1 has the lowest impact. These results corroborate the previous associations between amounts of plasma sHLA-G levels and 3′UTR haplotypes in healthy individuals and reinforce that 3′UTR typing may be a predictor of the genetic predisposition of an individual to express different levels of HLA-G.